Measurements of Higgs boson production by gluon-gluon fusion and vector-boson fusion using H → WW* → eνμν decays in pp collisions at √s=13 TeV with the ATLAS detector - Aad, Georges; Baltes, Lisa Marie; Bartels, Falk; Czurylo, Marta; Rio, Fernando del; Dittmeier, Sebastian; Dunford, Monica; Franchino, Silvia; Klassen, Martin; Mkrtchyan, Tigran; Ott, Philipp; Rassloff, Damir Fabrice; et al. (Physical review, 2023)
Higgs boson production via gluon-gluon fusion and vector-boson fusion in proton-proton collisions is measured in the H→WW∗→eνμν decay channel. The Large Hadron Collider delivered proton-proton collisions at a center-of-mass energy of 13 TeV between 2015 and 2018, which were recorded by the ATLAS detector, corresponding to an integrated luminosity of 139 fb−1. The total cross sections for Higgs boson production by gluon-gluon fusion and vector-boson fusion times the H→WW∗ branching ratio are measured to be 12.0±1.4 and 0.75 +0.19−0.16 pb, respectively, in agreement with the Standard Model predictions of 10.4±0.6 and 0.81±0.02 pb. Higgs boson production is further characterized through measurements of Simplified Template Cross Sections in a total of 11 kinematic fiducial regions.
Im Titel steht der Buchstabe "s" unter dem Wurzelsymbol
Gesehen am 16.01.2024
The ATLAS Collaboration: G. Aad, L.M. Baltes, F. Bartels, M.M. Czurylo, F. Del Rio, S.J. Dittmeier, M. Dunford, S. Franchino, M. Klassen, T. Mkrtchyan, P.S. Ott, D.F. Rassloff, S. Rodriguez Bosca, C. Sauer, A. Schoening, H-C. Schultz-Coulon, V. Sothilingam, R. Stamen, P. Starovoitov, L. Vigani, S.M. Weber, M. Wessels, J. Zinsser [und 2852 weitere]